The presence, severity, and onset of preeclampsia is associated with maternal interleukin-23 level: A case-control study - Forough Forghani; Nasrin Ranjbar; Danial Jahantigh (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Scientific evidence support that imbalance between inflammatory and anti-inflammatory cytokines play a critical role in preeclampsia (PE). Objective: To investigate the relationship between the maternal serum level of interleukin (IL)-23, a pro-inflammatory cytokine, PE and its severity risk was investigated. Materials and Methods: The case-control study included a total of 145 women counting 75 PE cases, 35 healthy pregnant and 35 healthy non-pregnant controls from Zahedan, southeast of Iran. The maternal levels of IL-23 in circulation were determined via enzyme-linked immunosorbent assay. Results: The maternal serum levels of IL-23 were increased in PE and its 2 subgroups severe PE and mild PE, so that these increases were significant in PE and severe PE, but not in mild PE compared with the controls (p < 0.001 and p < 0.001, p = 0.08, respectively). Besides, the maternal IL-23 serum level was statically significant in the early onset PE, but not in the late onset-PE group compared to healthy pregnant controls (p < 0.001, p = 0.46 respectively). Conclusion: The results of our study showed a positive association between IL-23 level and PE, especially in severe type and early onset PE, which suggests that IL-23 may be involved in the pathogenesis of this systemic syndrome.